2006
DOI: 10.1021/ic0608804
|View full text |Cite
|
Sign up to set email alerts
|

Hollow PbWO4 Nanospindles via a Facile Sonochemical Route

Abstract: Novel nanosized lead tungstate (PbWO4) hollow spindles were successfully synthesized, for the first time, via a Pluronic P123- (EO20PO70EO20-) assisted sonochemical process. The triblock copolymer acted as a structure-directing agent and played a key role in the formation of the hollow spindles. An in situ micelle templating mechanism has been proposed for the possible formation mechanism of the hollow nanostructure. The optical properties of the final products were investigated. It is exciting that the as-pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 64 publications
2
71
0
Order By: Relevance
“…In other words, the complex micellar aggregates formed by P123 acted as the templates for the formation of the NaNbO 3 1D nanowires, which is somewhat similar to the those in Ag 0.35 V 2 O 5 [26], PbWO 4 [35] and LaPO 4 cases [36]. The possible growth mechanism proposed here mainly involved four steps in sequence: (1) aggregation of micelles from P123 [38,39] (2) adsorption of niobium hydroxide (Nb 2 O 5 ÁxH 2 O) and Na ? ions onto the surface of Pluronic P123 micelle and the interbonding between Na ?…”
Section: Structures and Morphologymentioning
confidence: 56%
“…In other words, the complex micellar aggregates formed by P123 acted as the templates for the formation of the NaNbO 3 1D nanowires, which is somewhat similar to the those in Ag 0.35 V 2 O 5 [26], PbWO 4 [35] and LaPO 4 cases [36]. The possible growth mechanism proposed here mainly involved four steps in sequence: (1) aggregation of micelles from P123 [38,39] (2) adsorption of niobium hydroxide (Nb 2 O 5 ÁxH 2 O) and Na ? ions onto the surface of Pluronic P123 micelle and the interbonding between Na ?…”
Section: Structures and Morphologymentioning
confidence: 56%
“…[344] The intriguing formation mechanism was clearly identified to involve the formation of cubic template crystals made mainly of the surfactant (SDBS) molecules and subsequent growth of Co 3 O 4 nanocrystals on the template surface. Geng et al have synthesized PbWO 4 hollow nanospindles via a surfactant (P123)-mediated sonochemical route, [345] where the complex micellar aggregates formed from P123 and lead acetate around the cavitation bubbles are thought to serve as non-spherical soft templates. Yang et al have recently reported the synthesis of a siliceous structure with an unusual silkworm cocoonlike morphology using CTAB and perfluorooctanoic acid as cotemplates.…”
Section: Soft-templating Synthesis Of Non-spherical Hollow Structuresmentioning
confidence: 99%
“…Examples of successful sonochemical syntheses include TiO 2 , [56] ZnO, [57][58][59] CeO 2 , [60] MoO 3 , [61] V 2 O 5 , [62] In 2 O 3 , [63] ZnFe 2 O 4 , [64] PbWO 4 , [65,66] BiPO 4 , [67] and ZnAl 2 O 4 . [68] Yu and coworkers revealed that sonochemically prepared titania nanoparticles are more photocatalytically active than commercial titania nanoparticles (e.g., Degussa P25).…”
Section: Metal Oxidesmentioning
confidence: 99%